Blood urea nitrogen as an early predictor of severity in acute pancreatitis - Shah, Syed Mushtaq A.; Andrabi, Syed Aadil S.; Quraishi, Azhar-un-Nisa; Kumar, Ravi; Khan, Tahir S.; Shah, Aadil P.; Bhat, Bilal A.; Wani, Tajdin; Wani, Yaser H.; Bashir, Younis; Lone, Bilal A. (International Journal of Research in Medical Sciences, 2021)
Background: Acute pancreatitis presents as acute abdominal pain and is usually associated with raised pancreatic enzyme levels in the blood or urine. Aims and objectives of the study was to evaluate the role of serial BUN measurement as an early prognostic marker of acute pancreatitis. Methods: From each patient detailed history was taken, general and systemic examination were done and relevant investigations were conducted. BUN was repeated after 24 hours and the change in the level of BUN was noted. Imaging in the form of CT after 72 hours of admission were performed in each patient. The severity of acute pancreatitis was gauged by modified CTSI and the same was compared to the change in BUN values over first 24 hours of admission. Results: Mean BUN values at ‘0’ hour in severe acute pancreatitis and non-severe acute pancreatitis were 31.91±6.79 and 15.44±5.95 mg/dl, respectively. The difference between the two groups was statistically significant with p value of <0.001. Similarly, the difference in BUN values at ‘24’ hours between the two groups was statistically significant. BUN value ≥23 mg/dl at ‘0’ hour was found to be the optimal cut off for determining the severity of pancreatitis with sensitivity of 91.3%. BUN ≥25 mg/dl at 24 hours was found to be the optimal cut-off for determining the severity of acute pancreatitis with sensitivity of 95.7%. Conclusions: BUN as a single marker for acute pancreatitis can be useful as it is easy to perform and cheap marker to predict severity without the need for complex calculations.